Improvement Quality of Occupational Health and Safety Testing Laboratory Services Using Quality Function Deployment Method - Dimas Mukhlis Fathurohman; Wawan Herwanta; Intan Novitas Dewi; Krisnawanti Krisnawanti (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Efforts to improve the quality of OHS laboratory services this study aims to determine characteristics that have not met customer expectations and provide suggestions for OHS testing laboratory services. SERVQUAL and QFD methods are used in this study, which are based on 5 dimensions and 19 variables indicating customer expectations are greater than perceptions. Then the results in improving the quality of OHS laboratory test services required improvement of QFD analysis attributes withHouse of Quality second stage. The results of this study are in the form of main recommendations for developing integrated programs, namely increasing the intensity of communication to customers, holding comparative studies with overseas laboratories, renovating testing laboratories and facilities, training motivation and improving work culture, appointing suppliers for special testing equipment and reagents and distributing questionnaires. and discussions with consumers. Findings in research can assist management in improving service quality for customer satisfaction.